PENGARUH BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA APARATUR SIPIL NEGARA PADA DINAS PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA KOTA MAKASSAR - Muhammad Bakri; Muhammad Erfan (PIRSAP (Paser Institute for Scientific Research and Publications), 2024)
This study aims to test and analyze the effect of Workload and Work Environment on the Job Satisfaction of the State Civil Apparatus. The population in this study is the State Civil Apparatus (ASN) at the Makassar City Population Control and Family Planning Office as many as 62 civil servants. The sampling method used is Non Probability sampling and sample selection techniques, namely saturated samples. Data collection method through questionnaire distribution, then the data was analyzed using multiple linear regression analysis using SPSS 24 software. Based on partial results or t-tests, the workload variable shows the results of t-count (1,770) < t-table (2,000) so that it can be said that workload has a positive insignificant effect on job satisfaction, while the work environment variable shows the results that t-count (3,588) > t-table (2,000) so it is said that partially the work environment has a significant positive effect .